ANALISIS BUDAYA ORGANISASI DALAM MENINGKATKAN KEPUASAN KERJA KARYAWAN PADA TOKO RENTAL PERALATAN PRODUKSI FILM SUTINGYUK DI YOGYAKARTA - Aliya Aliya; Tarwijo Tarwijo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the role and effectiveness of organizational culture in improving employee job satisfaction at Sutingyuk, a film-production-equipment rental business in Yogyakarta. The research used a descriptive qualitative approach. Data were obtained through non-participant observation, semi-structured in-depth interviews, and documentation involving six informants representing the owner, administrative staff, warehouse staff, social media staff, and an intern. Data analysis followed the interactive Miles and Huberman model through data reduction, data display, and conclusion drawing and verification, while credibility was strengthened through source, technique, and time triangulation. The findings show that Sutingyuk’s organizational culture is organically built around trust, responsibility, family values, open communication, teamwork, work flexibility, and non-rigid professionalism. These values support job satisfaction by creating supportive supervision, close coworker relationships, opportunities for cross-functional learning, and room for employee initiative. Triangulation of ten analyzed indicators showed that most findings were mutually supportive or complementary. Nevertheless, the compensation dimension still requires improvement because one employee perceived an imbalance during periods of very high workload. Overall, Sutingyuk’s organizational culture is effective in improving job satisfaction, but a more transparent and proportional compensation system and clearer documentation of organizational values are needed to strengthen its sustainability.